Empowering Human Resources Within Training and Education About Musical Art at Pemuteran Village | Memberdayakan Sumber Daya Manusia Melalui Pelatihan dan Pendidikan Seni Karawitan di Desa Pemuteran - I Kadek Bagas Suradinata (Pusat Penerbitan LPPMPP ISI Denpasar, 2024)
This article is refered to a policy from government about Merdeka Belajar Kampus Merdeka (MBKM) within program Kuliah Kerja Nyata Tematik (KKNT) implemented at Pemuteran Village, Gerokgak District, Buleleng City. The workplan carried out is training about tabuh telu gegilakan, teaching the basic technique on playing Gong Kebyar, and training about tabuh telu lelambatan kreasi “Wási Silakrama” to childern’s Jelung Kumara Pemuteran Gong Kebyar Group JKP 3 and JKP 4. Especially for JKP 3, I applied creation tabuh telu lelambatan kreasi “Wási Silakrama” and tabuh telu gegilakan. The workplan held with some methods that writer used which is the imitation method came up by M. Gabriel Tarde, meguru panggul, observation, interview, and documentation. Apart from that, I also use the method of creation written by I Wayan Dibia in making the composition. The methods I've used have worked with frequent players in my program of work that I've done. I hope within two groups JKP 3 and JKP 4 is success and capable to come forth some creations which has been given for Sanggar Jelung Kumara anniversary held on July 8 2023. Hopefully this creation is very useful for two groups that will used for another festival, ceremony, etc.